Sistem Pakar Diagnosa Penyakit Pencernaan pada Manusia Menggunakan Metode Certainty Factor - Laita, Vera April; Efendi, Dwi Marisa; Ngajiyanto, Ngajiyanto (Universitas Multi Data Palembang, 2025)
Digestive diseases are one of the most common and diverse groups of diseases, covering a variety of conditions that affect the organs in the human digestive system. These diseases can range from mild disorders to serious conditions that require immediate medical attention. Delays in diagnosis and inappropriate treatment can lead to serious complications, as well as burden the health system. Digestive diseases are often difficult to diagnose because their symptoms can be similar to other conditions or vary from one individual to another. The examinations and tests needed for a proper diagnosis may also be unavailable or difficult to access. This study was conducted using the Development method using Extreme Programming, data collection, system analysis, database design, design of an expert system for diagnosing digestive diseases in humans using the certainty factor method, and the programming language used is Java programming. The development of this expert system for diagnosing digestive diseases in humans increases the accuracy and speed of the digestive disease diagnosis process and provides assistance to medical practitioners in making decisions related to diagnosis and treatment.